Dampak Pertumbuhan Penjualan, Profitabilitas dan Leverage Terhadap Nilai Perusahaan Pertambangan di Indonesia - Rujito Rujito; Giawan Nur Fitria (Journal of Innovative and Creativity, 2025)
This research aims to analyze the influence of sales growth, profitability, and leverage on firm value in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study is a quantitative research using an associative approach. The data utilized are secondary data obtained from the companies' annual financial statements. Sample selection was carried out using the purposive sampling method based on the criteria of mining companies that are consistently listed on the IDX and have complete financial statements throughout the observation period. Data analysis was performed using multiple linear regression with the aid of a statistical program. The results indicate that sales growth and profitability (ROA) have a positive influence on firm value, while leverage has a negative influence on firm value. Simultaneously, these three variables significantly influence firm value with a coefficient of determination of 35.4%. This suggests that an increase in sales growth and profitability can enhance firm value, while excessive use of debt may decrease it. These findings underscore the importance of balanced financial strategies in improving the performance and value of companies within the mining sector.